Effect of Compositions on Properties of Biocomposite Sheet Fabricated from Young Coconut Fiber and Star Apple Peel Powder - Rachakom, Ampika; Kongkeaw, Pongsathon; Namwong, Prachaya; Longkullabutra, Haruthai (KKU Science Journal, 2023)
This research aims to study the mechanical and physical properties of biocomposite sheet obtained from consumption waste of young coconut husks and star apple peel in order to enhance the value of these wastes by using as an interior decoration material. The fibers from young coconut husks were used as a reinforcement and mixed with the powder obtained from ground star apple peels as a filler ratio of 0%, 25%, 50% and 75% by weight. The biocomposite sheet was produced using the polymeric diphenylmethane diisocyanate (pMDI) as a binding agent. It was found that the impact strength and elongation decreased as the content of star apple powder increased, while the highest tensile strength and young’s modulus were observed in the biocomposite sheet with 25% and 50% by weight ratio of the star apple peel powder, respectively. Moreover, the physical characteristics of the specimens were investigated via optical microscopy (OM) and scanning electron microscopy (SEM). The micrographs reveal the distribution of star apple peel powder over the fibers of young coconut husk and the observed agglomeration of star apple peel powder increased with increasing amount of star apple peel powder.